(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Internet of things (IOT) is trending to become the element that connects several parameters of our every day lives to Internet. The analogy is Internet being the think engine, IOT enables to expand beyond the personal computers to every object that could be part of our daily lives, humans will be intergral part of the IOT system. Enterprise digital maturity drives the performance of organization and market inturn. Diversity index parameters is proposed for the measurement of a company's digital maturity based measurement data of different kinds of data sets. IOT can influence the capabilities of a company in terms of technology, tools that could influence the maturity assessment. Some of the IOT domain application areas are  Smart homes  Smart work environment  Security  Finance/Banking  Health care  Social technologies In this paper enterprise digital maturity measurement framework using IOT will be detailed. Diversity index related parameter such as Richness of data sets is proposed as a measure of the digital data richness for enterprise digital maturity benchmarking.